Visualizing the Shrimp Aquaculture Cycle Transforming Data into Informative Graphics - Naim, Sidrotun; Febrianti, Esther Asti; Halim, Jennifer; Elfan Zulvanian Rifky, Tristan (Journal of Sustainable Community Development (JSCD), 2025)
"Visualizing the Shrimp Aquaculture Cycle: Transforming Data into Informative Graphics" addresses the intricacies of shrimp farming through a novel approach—data visualization. As a critical component of the global seafood industry, shrimp aquaculture faces challenges ranging from disease management to environmental sustainability. This project seeks to enhance understanding and decision-making within the industry by transforming complex data into visually compelling graphics. We hope the project can reinforce the belief in the transformative power of data visualization as a tool for knowledge dissemination and advocacy in complex domains such as shrimp aquaculture. From pond or tank cultivation to disease control and harvesting, the project aims to empower stakeholders at every level, including shrimp farmers, industry professionals, researchers, and the wider public. By making use of clear and accessible graphics, the project facilitates the interpretation of essential factors such as water quality management that includes temperature, salinity, pH, bacteria and plankton concentrations for three to four months of the shrimp aquaculture cycle. The objective is not only to simplify complex data but also to promote awareness and prevention from various disease threats by giving an early warning sign.